2016
DOI: 10.1016/j.jes.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the characteristics of particulate matters captured by urban plants using an automatic approach

Abstract: It is widely accepted that urban plant leaves can capture airborne particles. Previous studies on the particle capture capacity of plant leaves have mostly focused on particle mass and/or size distribution. Fewer studies, however, have examined the particle density, and the size and shape characteristics of particles, which may have important implications for evaluating the particle capture efficiency of plants, and identifying the particle sources. In addition, the role of different vegetation types is as yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Also biomagnetic monitoring of atmospheric pollution accumulated on biological surfaces is a growing application in the field of environmental magnetism, providing a record of location-specific, timeintegrated air quality information, mainly through saturation isothermal remanent magnetization (SIRM) (Hofman et al 2017), but no information on particle morphology can be obtained. Using leaves as in situ, low-cost, highly spatially resolved passive samplers for monitoring urban PM, scanning electron microscopy combined with energy dispersed X-ray spectroscopy (SEM/EDX) has been reported to be the most appropriate analytical technique to study PM size, number and chemical composition directly on the leaves of urban trees (Wang et al 2015;Yan et al 2016;Baldacchini et al 2017) or shrubs (Weerrakkody et al 2018;Shao et al 2019). However, the spatial scale of a SEM/EDX analysis (typically hundreds of microns square of leaf area per sample) is very limited compared to the more commonly used VF (typically many leaves per sample) and no quantitative estimation of the PM amount in terms of mass has been reported by this technique up to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also biomagnetic monitoring of atmospheric pollution accumulated on biological surfaces is a growing application in the field of environmental magnetism, providing a record of location-specific, timeintegrated air quality information, mainly through saturation isothermal remanent magnetization (SIRM) (Hofman et al 2017), but no information on particle morphology can be obtained. Using leaves as in situ, low-cost, highly spatially resolved passive samplers for monitoring urban PM, scanning electron microscopy combined with energy dispersed X-ray spectroscopy (SEM/EDX) has been reported to be the most appropriate analytical technique to study PM size, number and chemical composition directly on the leaves of urban trees (Wang et al 2015;Yan et al 2016;Baldacchini et al 2017) or shrubs (Weerrakkody et al 2018;Shao et al 2019). However, the spatial scale of a SEM/EDX analysis (typically hundreds of microns square of leaf area per sample) is very limited compared to the more commonly used VF (typically many leaves per sample) and no quantitative estimation of the PM amount in terms of mass has been reported by this technique up to date.…”
Section: Introductionmentioning
confidence: 99%
“…Each selected image was analysed using Gwyddion open source software (Necǎs et al 2012). By applying a colour threshold based grain analysis (Yan et al 2016;Baldacchini et al 2017), the number of particles in the image, together with the aerodynamic diameter (diameter of the equivalent sphere, deq) of each particle, were obtained. Particles with a deq comparable with the size of a single pixel (0.146 μm) were excluded, resulting in a lower cut-off at about 0.3 μm in the diameter of the analysed particles.…”
mentioning
confidence: 99%
“…So, the ability of the leaves to capture and accumulate particle matters differs significantly among plants. And this varies greatly from tree to tree and plant species [72]. Moreover, rougher leaf surfaces, larger differences in the depths of creases, densely ridged grooves, lower stomatal densities, and more waxes are more conducive for the capture and adsorption of particle matters [73][74][75][76].…”
Section: Mechanisms and Background Techniquesmentioning
confidence: 99%
“…In Beijing, China, an experiment on PM capture capacity was conducted on Rosa xanthina, a shrub, Broussonetia papyrifera, a broadleaf tree, and Pinus bungeana, a conifer, and found that shrubs had the greatest PM capture efficiency (Yan et al, 2016). Sillars-Powell et al (2020) compared PM accumulation on leaves of shrubs including Hedera helix and Rubus fruticosu, and reported that the dense canopy of the two plants reduced airflow, and played a role in preventing the movement of and immobilizing PM.…”
Section: Introductionmentioning
confidence: 99%